2021
DOI: 10.1016/j.jhin.2021.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Olanexidine gluconate formulations as environmental disinfectants for enveloped viruses infection control

Abstract: This study investigated the potential of olanexidine gluconate as environmental disinfectant against enveloped viruses in the suspension test and three non-porous surface tests. In the suspension test, olanexidine gluconate showed immediate virucidal activity. In addition, non-porous surface tests demonstrated that, although the immediate effect of aqueous formulations was weak, the final virucidal efficacy outcompeted that of ethanol for disinfection. Furthermore, the effectiveness of olanexidine gluconate pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Nine studies validated the spectrum: seven for bacteria and fungi 20 , 21 , 22 , 23 , 24 , 25 , 28 and four for viruses. 28 , 32 , 33 , 34 Several studies 20 , 23 , 25 , 28 used the minimum bactericidal concentration (MBC) at which bacterial growth did not occur as an indicator of the bactericidal effect of skin disinfectants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies validated the spectrum: seven for bacteria and fungi 20 , 21 , 22 , 23 , 24 , 25 , 28 and four for viruses. 28 , 32 , 33 , 34 Several studies 20 , 23 , 25 , 28 used the minimum bactericidal concentration (MBC) at which bacterial growth did not occur as an indicator of the bactericidal effect of skin disinfectants.…”
Section: Resultsmentioning
confidence: 99%
“…Imai et al. 34 also reported on the potential usage of OLG formulations as environmental disinfectants for the control of infections by enveloped viruses (influenza A [H1N1], human coronavirus, feline infectious peritonitis virus, human herpesvirus, and respiratory syncytial virus).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical trials, Obara et al reported that 1.5% OLG significantly reduced the occurrence of overall surgical site infections (SSIs) and superficial SSIs compared with PVP-I in cleancontaminated surgery 2 . Additionally, the findings of previous studies showed that 1.5% olanexidine-containing 70% ethanol formulation for hand hygiene (OLG hand rub; OLG-HR) was more virucidal than ethanol against human noroviruses 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Olanedine antiseptic solution efficacy was evaluated in a randomized, controlled clinical trial in Japan, and surgical site infections following gastrointestinal surgery occurred less frequently with its use than with the use of commercial antiseptics povidone-iodine and chlorhexidine ( 15 , 17 , 18 ). Its bactericidal efficacy as a topical antiseptic led to its proposed use for preoperative skin preparation prior to surgery ( 15 ) and as an environmental disinfectant for the prevention of nosocomial transmission of enveloped viruses, including influenza A viruses, respiratory syncytial viruses, and coronaviruses ( 19 ). Here, we tested the effectiveness, and explored the mechanism of action of olanexidine gluconate-containing hand rub (OLG-HR) on HuNoV infectivity.…”
Section: Introductionmentioning
confidence: 99%